Algoritmo para localização de faltas em linhas de transmissão baseado na teoria de estimação de estados - Queiroz, Luann Georgy Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Fault localization algorithms are frequently used in electrical power systems with the objective of accurately estimating the location of a short circuit, optimizing the process of maintenance and restoration of the network. Thus, the performance of this type of algorithm can directly influence the continuity and operation of the system, reducing the costs caused by shutdowns and consequently increasing the reliability of the electrical system. This paper presents the development of a fault localization methodology in transmission lines using the state estimation theory to indicate the most probable location of occurrence of faults considering possible errors in voltage and current measurements. The methodology was basically divided into: obtaining voltage and current waveforms through the simulated electrical system in the ATP software; verification of the influences of instrument transformer errors on localization methodologies based on fundamental phasors; and development and performance analysis of the proposed fault location estimator. The results showed that the proposed methodology, in comparison with Oliveira Neto (2018), allowed a reduction of fault location error values, where this improvement was manifested more expressively when only the potential transformers (TPs)
Keywords: Linhas de Transmissão; Localização de Faltas; Estimação de Estados; Transformadores para Instrumentos; Lines Transmission; Fault Location; State Estimation; Instrument Transformer; ENGENHARIAS::ENGENHARIA ELETRICA